2022
DOI: 10.1155/2022/7981637
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Expression of NUMB in Peripheral Blood with Acute Myocardial Infarction

Abstract: Objective. Our study’s goal was to find out acute myocardial infarction (AMI) patients’ NUMB gene expression patterns and to evaluate its role as a diagnostic marker for AMI detection. Methods. Peripheral blood was drawn from 124 individuals who had an AMI and 115 patients who had stable coronary artery disease (SCAD). The real-time quantitative polymerase chain reaction was used to measure the mRNA expression level of the NUMB gene in peripheral blood. Results. The AMI group’s NUMB gene expression was 0.906 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In terms of cardiovascular pathologies, NUMB has been proposed as an indicator of an increased risk of coronary artery disease. In this case, lower NUMB expression indicates a higher risk of developing the disease [208]. In addition, NUMB has also been proposed as a therapeutic candidate for muscle and cardiac regeneration, as well as for congenital heart disease [209,210].…”
Section: Numb As a Therapeutic Tool For Various Pathologiesmentioning
confidence: 99%
“…In terms of cardiovascular pathologies, NUMB has been proposed as an indicator of an increased risk of coronary artery disease. In this case, lower NUMB expression indicates a higher risk of developing the disease [208]. In addition, NUMB has also been proposed as a therapeutic candidate for muscle and cardiac regeneration, as well as for congenital heart disease [209,210].…”
Section: Numb As a Therapeutic Tool For Various Pathologiesmentioning
confidence: 99%
“…Peripheral blood can be used as a window to evaluate diseases [ 48 , 49 , 50 ]. It is convenient for sampling and causes minimal harm [ 51 ].…”
Section: Sampling Positionmentioning
confidence: 99%
“…The expression level of the adior2 gene, for example, is linked to the advancement of coronary atherosclerosis [ 70 ]. Meng et al revealed that numb ABCB1, ACSL1, ZHHC9, and other genes have important roles in the pathogenesis of atherosclerosis [ 71 , 72 , 73 , 74 ]. Furthermore, a study from the University of Washington discovered that the SVEP1 gene causes atherosclerosis in the absence of cholesterol [ 75 ].…”
Section: Gene and Protein Markersmentioning
confidence: 99%